Disproportionality analysis of quinolone safety in children using data from the FDA adverse event reporting system (FAERS) - Kong, Wenqiang; Mao, Wei; Zhang, Lin; Wu, Yanyan (Frontiers in Pediatrics, 2023)
Background: Quinolones are widely prescribed for the treatment or prevention of infectious diseases in children. To gain further insight into quinolone-associated AEs in children and better protect pediatric patients, continued surveillance of safety data is essential. The purpose of this study was to characterize the safety profiles of quinolone-associated AEs in children by mining the FDA adverse event reporting system (FAERS). Methods: FAERS reports from quarter 1 of 2004 to quarter 1 of 2022 were included in the study. The Medical Dictionary for Regulatory Activities (MedDRA) was used to identify adverse events. Reporting odds ratios (ROR) corresponding 95% confidence intervals (CIs) and information component (IC) along with 95% CIs were calculated to detect drug–AE pairs with higher-than-expected reporting rates within the FAERS. Significance was considered when both lower 95% CI bounds were > 1. Results: After inclusion criteria were applied, a total of 4,704 reports associated with quinolones were considered. Most FAERS reports associated with ciprofloxacin (N=2,706) followed by levofloxacin (N= 1,191), moxifloxacin (N= 375), oflaxacin (N= 245) and ozenoxacin (N= 187). The most common age group was 12–18 years. The median weight was 39.0 kilogram. The adverse effects of quinolones primarily included gastrointestinal symptoms such as vomiting, diarrhea, abdominal pain, and nausea. Other quinolones-associated signal detection results for children were as follows: blood and lymphatic system disorders such as febrile neutropenia, cardiac disorders such as cardiac arrest and tachycardia, nervous system disorders such as neuropathy peripheral, seizure and somnolence, musculoskeletal and connective tissue disorders such as arthralgia and psychiatric disorders such as suicide. Conclusion: This study provided additional evidence with respect to quinolones-related AEs for children. Generally, the findings of this study are compatible with AEs recorded in package inserts. The AEs of ozenoxacin for children have not been previously reported.